Weight and BMI Changes Following Initiation of Emtricitabine/Tenofovir Alafenamide Co-Formulated with Darunavir or Co-Administered with Dolutegravir in Overweight or Obese, ART-Naïve People Living with HIV-1 - Donga P; Emond B; Rossi C; Bookhart BK; Lee J; Caron-Lapointe G; Wei F; Lafeuille MH (Dove Medical Press, 2023)
Prina Donga,1 Bruno Emond,2 Carmine Rossi,2 Brahim K Bookhart,1 Johnnie Lee,1 Gabrielle Caron-Lapointe,2 Fangzhou Wei,3 Marie-Hélène Lafeuille2 1Janssen Scientific Affairs, LLC, Titusville, NJ, USA; 2Analysis Group, Inc, Montréal, QC, Canada; 3Analysis Group, Inc, Menlo Park, CA, USACorrespondence: Carmine Rossi, Analysis Group, Inc, 1190 Avenue des Canadiens-de-Montréal, Tour Deloitte, Suite 1500, Montréal, QC, H3B 0G7, Canada, Tel +1 514-871-4233, Email carmine.rossi@analysisgroup.comIntroduction: Integrase strand transfer inhibitor-based regimens (eg, containing dolutegravir [DTG]) are associated with weight/body mass index (BMI) increases among people living with HIV-1 (PLWH). Assessing antiretroviral therapy (ART)-related weight/BMI changes is challenging, as PLWH may experience return-to-health weight gain as a result of viral suppression. This retrospective, longitudinal real-world study compared weight/BMI outcomes among overweight/obese (BMI ≥ 25 kg/m2; thus excluding return-to-health weight/BMI changes), treatment-naïve PLWH who initiated darunavir (DRV)/cobicistat (c)/emtricitabine (FTC)/tenofovir alafenamide (TAF) or DTG + FTC/TAF.Methods: Treatment-naïve PLWH with BMI ≥ 25 kg/m2 who initiated DRV/c/FTC/TAF or DTG + FTC/TAF (index date) had ≥ 12 months of baseline observation and ≥ 1 weight/BMI measurement in baseline and post-index periods in the Symphony Health IDV® database (07/17/2017- 12/31/2021) were included. Inverse probability of treatment weighting (IPTW) was used to balance differences in baseline characteristics between cohorts. On-treatment time-to-weight/BMI increases ≥ 5% were compared between cohorts using weighted adjusted Cox models.Results: Post-IPTW, 76 overweight/obese DRV/c/FTC/TAF-treated (mean age = 51.2 years, 30.7% female, 35.6% Black, mean baseline BMI = 33.2 kg/m2) and 88 overweight/obese DTG + FTC/TAF-treated PLWH (mean age = 51.5 years, 31.4% female, 31.4% Black, mean baseline BMI = 32.7 kg/m2) were included. The median [interquartile range] time from ART initiation to weight/BMI increase ≥ 5% was shorter for the DTG + FTC/TAF cohort (21.8 [9.9, 32.3] months) than the DRV/c/FTC/TAF cohort (median and interquartile times not reached; Kaplan-Meier rate at 21.8 months = 20.8%). Over the entire follow-up, overweight/obese PLWH initiating DTG + FTC/TAF had a more than twofold greater risk of experiencing weight/BMI increase ≥ 5% compared to those initiating DRV/c/FTC/TAF (hazard ratio [95% confidence interval]=2.43 [1.02; 7.04]; p = 0.036).Conclusion: Overweight/obese PLWH who initiated DTG + FTC/TAF had significantly greater risk of weight/BMI increase ≥ 5% compared to similar PLWH who initiated DRV/c/FTC/TAF and had shorter time-to-weight/BMI increase ≥ 5%, suggesting a need for additional monitoring to assess the risk of weight gain-related cardiometabolic disease.Keywords: human immunodeficiency virus, weight gain, BMI, darunavir, dolutegravir, observational study